INCONVENCIONALIDAD DE LA PRISIÓN PREVENTIVA OFICIOSA EN MÉXICO - Martínez Lazcano, Alfonso Jaime (2021)
The reform of article 19 of the Mexican Constitution increases crimes, which do not allow the legal operator to weigh or reason, not only violates human rights but also violates the division of powers, by incorporating more crimes that provide for unofficial preventive detention, an addition contrary to the culture generated by the Inter-American Human Rights System and various organizations of the United Nations, as they are contrary, among other provisions, to article 9.3 of the International Covenant on Civil and Political Rights and paragraph 8.2 of the American Convention on Human Rights which provides for the principle of presumption of innocence.